PD-L1 Under Regulation of miR-429 Influences the Sensitivity of Gastric Cancer Cells to TRAIL by Binding of EGFR - Lv, Jinqi; Guo, Tianshu; Qu, Xiujuan; Che, Xiaofang; Li, Ce; Wang, Shuo; Gong, Jing; Wu, Peihong; Liu, Yang; Liu, Yunpeng; Xu, Ling (Frontiers in Oncology, 2020)
TRAIL has received extensive attention as a cancer therapeutic due to its high propensity for tumor targeting with minimal toxicity to healthy tissue. Gastric cancer (GCa) cells show high levels of TRAIL resistance. EGFR antagonizes TRAIL-induced apoptosis, but the mechanisms of these effects remain unclear. Our past research confirms TRAIL resistant (BGC823 and SGC7901) and TRAIL sensitive cells (HGC27 and MKN45). MiR-429 associated with TRAIL sensitivity was screened using microRNA arrays. The transfection of mimics and inhibitors confirmed that miR-429 negatively correlated with GCa TRAIL resistance. The target gene of miR-429 was identified as PD-L1 which positively correlated with TRAIL resistance through gene silencing and recovery experiments. Using CO-Ips and proximity ligation assay, we demonstrated that the pro-survival effects of PD-L1 are mediated through the binding and activation of EGFR. Cell viability experiments demonstrated that PD-L1 is key to the maintenance of cell viability in TRAIL treated cells. This indicated that PD-L1 binds to and participates in EGFR activation through miR-429 regulation to antagonize TRAIL-induced apoptosis. This provides a new theoretical basis for the combination of the EGFR monoclonal antibodies including cetuximab, PD-L1 inhibitors and human recombinant TRAIL in gastric cancer therapy, and can filter patients who are currently sensitive to TRAIL treatment.